2012
DOI: 10.1161/jaha.112.002634
|View full text |Cite
|
Sign up to set email alerts
|

Renalase Lowers Ambulatory Blood Pressure by Metabolizing Circulating Adrenaline

Abstract: BackgroundBlood pressure is acutely regulated by the sympathetic nervous system through the action of vasoactive hormones such as epinephrine, norepinephrine, and dopamine. Renalase, a recently described, secreted flavoprotein, acutely decreases systemic pressure when administered in vivo. Single‐nucleotide polymorphisms present in the gene are associated with hypertension, cardiac disease, and diabetes. Although renalase's crystal structure was recently solved, its natural substrate(s) remains undefined.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 21 publications
5
135
1
2
Order By: Relevance
“…[1][2][3] As a biological macromolecule strongly associated with the sympathetic nervous system, renalase has been intensively studied since its discovery. [4][5][6] Insulin resistance (IR) is a key feature of type 2 diabetes mellitus (T2DM). 7 In some T2DM patients, CA levels in blood circulation are increased.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As a biological macromolecule strongly associated with the sympathetic nervous system, renalase has been intensively studied since its discovery. [4][5][6] Insulin resistance (IR) is a key feature of type 2 diabetes mellitus (T2DM). 7 In some T2DM patients, CA levels in blood circulation are increased.…”
Section: Introductionmentioning
confidence: 99%
“…They hypothesized that in this condition a more activated renalase was synthesized to cope with the increased NA levels. Recently, renalase was suggested to preferentially metabolize the circulating A, and its capacity to decrease blood pressure is directly correlated to this particular enzymatic activity [29,30]. However, to metabolize A, renalase uses a mechanism that is different from that exhibited by the monoamine oxidase (MAO).…”
Section: Discussionmentioning
confidence: 99%
“…Renalase is related to monoamine oxidase A with only 13% of amino acid identity [1]. As mentioned before, renalase is supposed to metabolise circulating in blood catecholamines, but its activity against dopamine, epinephrine, and norepinephrine remains unclear [1,13]. Moreover, renalase activity measurements need further explanation.…”
Section: Renalase and Cvdmentioning
confidence: 98%
“…Wu et al [12] noticed that renalase knock-out mouse was hypertensive and tachycardiac and had higher catecholamine levels compared to wild type mouse. One year later Desir et al [13] observed a fall in blood pressure after subcutaneous administration of renalase in 5/6 nephrectomised rats. The same effect was observed after administration of 5 mg/kg enalapril.…”
Section: Renalase and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation